A Discrete-Time Dynamical System of Wild Mosquito Population with Allee Effects - adults, We study a discrete-time dynamical system of wild mosquito population with parameters: - the birth rate of; rate, - maximum emergence; adults, - the death rate of; state., - Allee effects. We prove that if then the mosquito population dies and if holds then extinction or survival of the mosquito population depends on their initial (Discontinuity, Nonlinearity, and Complexity, 2026)
We study a discrete-time dynamical system of wild mosquito population with parameters: $β$ - the birth rate of adults; $α$ - maximum emergence rate; $μ>0$ - the death rate of adults; $γ$ - Allee effects. We prove that if $γ≥\frac{α(β-μ)}{μ^2}$ then the mosquito population dies and if $γ